Study of multiferroic materials - Figueiras, Fábio Gabriel Nazário (2013)
The present PhD work aims the research and development of materials that exhibit multiferroic properties, in particular having a significant interaction between ferromagnetism and ferroelectricity; either directly within an intrinsic single phase or by combining extrinsic materials, achieving the coupling of properties through mechanic phenomena of the respective magnetostriction and piezoelectricity. These hybrid properties will allow the cross modification of magnetic and electric polarization states by the application of cross external magnetic and/or electric fields, giving way to a vast area for scientific investigation and potential technological applications in a new generation of electronic devices, such as computer memories, signal processing, transducers, sensors, etc. Initial experimental work consisted in chemical synthesis of nano powders oxides by urea pyrolysis method: A series of ceramic bulk composites with potential multiferroic properties comprised: of LuMnO3 with La0.7Sr0.3MnO3 and BaTiO3 with La0.7Ba0.3MnO3; and a series based on the intrinsic multiferroic LuMn1-zO3 phase modified with of Manganese vacancies. The acquisition of a new magnetron RF sputtering deposition system, in the Physics Department of Aveiro University, contributed to the proposal of an analogous experimental study in multiferroic thin films and multilayer samples. Besides the operational debut of this equipment several technical upgrades were completed like: the design and construction of the heater electrical contacts; specific shutters and supports for the magnetrons and for the substrate holder and; the addition of mass flow controllers, which allowed the introduction of N2 or O2 active atmosphere in the chamber; and the addition of a second RF generator, enabling co-deposition of different targets. Base study of the deposition conditions and resulting thin films characteristics in different substrates was made from an extensive list of targets. Particular attention was given to thin film deposition of magnetic phases La1-xSrxMnO3, La1-xBaxMnO3 and Ni2+x-yMn1-xGa1+y alloy, from the respective targets: La0.7Sr0.3MnO3, La0.7Ba0.3MnO3; and NiGa with NiMn. Main structural characterization of samples was performed by conventional and high resolution X-Ray Diffraction (XRD); chemical composition was determined by Electron Dispersion Spectroscopy (EDS); magnetization measurements recur to a Vibrating Sample Magnetometer (VSM) prototype; and surface probing (SPM) using Magnetic-Force (MFM) and Piezo-Response (PFM) Microscopy. Results clearly show that the composite bulk samples (LuM+LSM and BTO+LBM) feat the intended quality objectives in terms of phase composition and purity, having spurious contents below 0.5 %. SEM images confirm compact grain packaging and size distribution around the 50 nm scale. Electric conductivity, magnetization intensity and magneto impedance spreading response are coherent with the relative amount of magnetic phase in the sample. The existence of coupling between the functional phases is confirmed by the Magnetoelectric effect measurements of the sample “78%LuM+22%LSM” reaching 300% of electric response for 1 T at 100 kHz; while in the “78%BTO+22%LBM” sample the structural transitions of the magnetic phase at ~350 K result in a inversion of ME coefficient the behavior. A functional Magneto-Resistance measurement system was assembled from the concept stage until the, development and operational status; it enabled to test samples from 77 to 350 K, under an applied magnetic field up to 1 Tesla with 360º horizontal rotation; this system was also designed to measure Hall effect and has the potential to be further upgraded. Under collaboration protocols established with national and international institutions, complementary courses and sample characterization studies were performed using Magneto-Resistance (MR), Magneto-Impedance (MZ) and Magneto-Electric (ME) measurements; Raman and X-ray Photoelectron Spectroscopy (XPS); SQUID and VSM magnetization; Scanning Electron Microscopy (SEM) and Rutherford Back Scattering (RBS); Scan Probe Microscopy (SPM) with Band Excitation Probe Spectroscopy (BEPS); Neutron Powder Diffraction (NPD) and Perturbed Angular Correlations (PAC). Additional collaboration in research projects outside the scope of multiferroic materials provided further experience in sample preparation and characterization techniques, namely VSM and XPS measurements were performed in cubane molecular complex compounds and enable to identify the oxidation state of the integrating cluster of Ru ions; also, XRD and EDS/SEM analysis of the acquired targets and substrates implied the devolution of some items not in conformity with the specifications. Direct cooperation with parallel research projects regarding multiferroic materials, enable the assess to supplementary samples, namely a preliminary series of nanopowder Y1-x-yCaxØyMn1O3 and of Eu0.8Y0.2MnO3, a series of micropowder composites of LuMnO3 with La0.625Sr0.375MnO3 and of BaTiO3 with hexagonal ferrites; mono and polycrystalline samples of Pr1-xCaxMnO3, La1-xSrxMnO3 and La1-xCaxMnO3.